(untitled) (Global Journals of Research in Engineering, 2013)
- Non-linear filters are large family of filters used in signal and image processing. They have found numerous applications such as in digital image restoration, speech processing and coding, digital TV applications, etc. In this paper, three-point median filter is designed using singleelectron transistor. In single-electron transistor bits of information are represented by the presence or absence of electrons at conducting islands. Single Electron Transistor (SET), distinguished by a very small device size low power dissipation, high speed and high performance, is one of the most promising nano electronics devices to replace conventional CMOS. The SET technology offers the ability to control the motion of individual electrons in the designed circuits . The Non-linear filter is simulated using a Monte Carlo technique by PSPICE9.1 and their correct and stable logical operation is confirmed.